Downstream Stockpiling of Steel Inventories and Artificial Demand: The Case of Saudi Arabia - AlFayad, Dr. Fadye S. (Archives of Business Research, 2016)
This research study has analyzed how downstream stockpiling within the steel industry and its supply channel actually disrupts the efficiency of the supply chain. The premise upon which this study has been approached is one that states that such downstream stockpiling tends to create artificial demand both upstream in the supply chain and in the marketplace. This subject is examined within the context of the Saudi Arabia steel industry and how this type of phenomenon resulted in steel shortages within the Saudi steel market. The study’s data found that the Saudi steel market is expected to expand at a compound annual growth rate (CAGR) of some 11.7% over the next several years. Furthermore, Saudi Arabia has experienced a number of periods of shortages in the supply of steel products. These steel shortages were shown to have resulted in spikes in the price of the commodity for supply chain participants and consumers. The data and information in this study all support the notion that a certain amount of volatility within Saudi Arabia with respect to the steel industry and the supply chain exists. The Kingdom has attempted to compensate for supply chain hoarding and stockpiling by increasing its domestic output which can be utilized to smooth out supply shortages within the supply chain. The study found that the actual result of this rationale in developing buffers is that it quickly transitions into stockpiling. This in turn results in further negative outcomes such as bullwhip effects up and downstream in the supply channel. The information that has been studied revealed that this point at which buffer inventories cross over into what is referred to as hoarding territory can be found through a specific formula. This formula was shown to be the EOQ calculation or the economic order quantity. This calculation utilizes real demand times in the supply chain along with re- ordering costs divided by the product carrying cost to arrive at an accurate figure. In practice, if the EOQ finds that the annual total steel expense exceeds the annual carrying costs for the inventory then there is excessive inventory or stockpiling in the supply chain. The study has also found that the Saudi Arabia supply chain requires a more efficient way to organize the product flow through the entire steel supply chain. This more efficient methodology would be a supply chain that is organized through the fast-moving, slow-moving and non-moving methodology. This methodology ensures that slow-moving steel products like crude steel, flats and galvanized steel are assigned to the slow- moving category and inventory these items at much lower levels.